2014
DOI: 10.1111/gcb.12572
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and peat type control CO2 and CH4 production in Alaskan permafrost peats

Abstract: Controls on the fate of ~277 Pg of soil organic carbon (C) stored in permafrost peatland soils remain poorly understood despite the potential for a significant positive feedback to climate change. Our objective was to quantify the temperature, moisture, organic matter, and microbial controls on soil organic carbon (SOC) losses following permafrost thaw in peat soils across Alaska. We compared the carbon dioxide (CO2 ) and methane (CH4 ) emissions from peat samples collected at active layer and permafrost depth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
139
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 182 publications
(153 citation statements)
references
References 80 publications
(107 reference statements)
12
139
2
Order By: Relevance
“…At the same time, the difference of Q 10 values under AE and AN conditions also demonstrated that soil carbon became more liable to microbes under O 2 abundant environment (Lee et al, 2012;Wang et al, 2013). Though the effect of temperature and O 2 on Rs had been well studied in other peatlands (Knoblauch et al, 2013;Moore and Dalva, 1997;Szafranek-Nakonieczna and Stêpniewska, 2014;Treat et al, 2014;Wang et al, 2013), our results from an area of midlatitude and high altitude were different from others. Rs increase with oxidizing or 10°C warming was much lower in our study than in other incubation studies (85.8-226.1% and 128.9-200%) (Table S1), indicating the lower sensitivity of peat in this area to warming and oxidizing, which can be explained by the different climate (temperature and precipitation) and vegetation in our study area from those of the others (Table S1).…”
Section: Effects Of Temperature and Oxygencontrasting
confidence: 72%
See 4 more Smart Citations
“…At the same time, the difference of Q 10 values under AE and AN conditions also demonstrated that soil carbon became more liable to microbes under O 2 abundant environment (Lee et al, 2012;Wang et al, 2013). Though the effect of temperature and O 2 on Rs had been well studied in other peatlands (Knoblauch et al, 2013;Moore and Dalva, 1997;Szafranek-Nakonieczna and Stêpniewska, 2014;Treat et al, 2014;Wang et al, 2013), our results from an area of midlatitude and high altitude were different from others. Rs increase with oxidizing or 10°C warming was much lower in our study than in other incubation studies (85.8-226.1% and 128.9-200%) (Table S1), indicating the lower sensitivity of peat in this area to warming and oxidizing, which can be explained by the different climate (temperature and precipitation) and vegetation in our study area from those of the others (Table S1).…”
Section: Effects Of Temperature and Oxygencontrasting
confidence: 72%
“…the increment at each depth was unequable and differed much with depth, which may reflect the variation of soil substrate among all profiles (Treat et al, 2014). The fact that the increments at 0-20 cm and 60-80 cm were higher than other layers may demonstrate that the carbon at these two layers is intrinsically labile and has higher potential decomposability (Oechel et al, 1998).…”
Section: Variations Among the Whole Depth Profilementioning
confidence: 94%
See 3 more Smart Citations